Adaptive and sliding mode friction-resilient machine tool positioning – Cascaded control revisited. (1st October 2019) - Papageorgiou, Dimitrios; Blanke, Mogens; Niemann, Hans Henrik; Richter, Jan H.
Highlights: Design and comparison of cascaded nonlinear controllers for machine tools axes. Controller evaluation with respect to accuracy and resilience to varying friction. Combination of quantitative and qualitative criteria for the comparison. Super-twisting sliding-mode controller is superior to all other considered schemes. Direct-position controllers have good performance but greater design complexity. Abstract: Needs for high-accuracy tool positioning and accurate trajectory following have renewed the focus on controller design for machine tools. While state-of-the-art solutions, based on Proportional (P) and Proportional-Integral (PI) cascades, achieve sufficient nominal performance, axis positioning accuracy quickly degrades in the presence of additional wear-related friction. Sliding-mode and nonlinear adaptive controllers with no cascaded architecture can alleviate such performance deterioration at the cost, however, of significantly increased design complexity. This is mainly due to the fact that such architectures facilitate addressing more nonlinear phenomena, such as load dynamic friction. This paper investigates three nonlinear controllers with cascaded architecture for machine tool axis positioning. A comparative analysis of the positioning solutions is carried out and it is shown that a cascaded scheme comprising a proportional and a super-twisting sliding-mode controller offers superior friction-resilient axis positioning. Moreover, its design complexity is comparable to that of the conventional P-PI solution. Experimental results obtained from a single-axis test setup equipped with commercial industrial equipment validate the theoretical findings.